Pengelolaan Stakeholder PT Securty Operation Group melalui Kegiatan Pelayanan di tengah Pandemi Covid-19 - Muhammad Faisal Kusuma Yudha Rinalzi; M subur Drajat (UNISBA Press, 2022)
Abstract. The spread of Covid-19 in Indonesia has caused a public commotion. It has been recorded that 2.47 million positive cases have been recorded on June 8, 2021. This has greatly impacted all industrial sectors. One of them is PT SOG INDONESIA, one of the companies engaged in security technology which is experiencing considerable obstacles. Given the pandemic situation, various sectors have to control all their operations from home, while PT SOG has not been optimal in managing media technology. The method used by researchers in describing and finding the model in this study is qualitative with a case study approach using stakeholder management theory, social media technology, digital services, and service excellence as a reference theory. The findings of this study reveal that stakeholder management is carried out by PT SOG Indonesia is able to improve service excellence, online media management and Employment Management. The stakeholder management strategies carried out by PT SOG Indonesia are 1) Stakeholder Management (Employee); 2) Recruitment staff; 3) Excellent Service; 4) consumer proximity; 5) social media management; 6) optimizing electronic services. Abstrak. Penyebaran Covid-19 di Indonesia membuat kegaduhan public. Tercatat sudah mencapai 2,47 juta kasus positif pada tanggal 8 juni 2021. Hal ini sangat berdampak pada seluruh sector industry, salah satunya pada PT SOG INDONESIA, perusahaan yang bergerak pada bidang teknologi keamanan yang mengalami hambatan yang cukup besar. Pandemi mengharuskan berbagai sektor mengontrol seluruh operasionalnya dari rumah, sedangkan PT SOG belum maksimal menggunakan media teknologi sebagai penungjang dalam melakukan pelayanan. Metode yang digunakan peneliti dalam penelitian ini ialah kualitatif dengan pendekatan studi kasus. Teori manajemen stakeholders, teknologi sosial media, pelayanan digital, dan service excellent sebagai pijakan dalam penelitian ini. Hasil temuan penelitian ini mengungkapkan bahwa pelayanan dalam pengelolaan stakeholder yang dilakukan oleh PT SOG Indonesia mampu meningkatkan service excellent, pengelolaan media online dan Pengelolaan Employe. Adapun strategi pengelolaan stakeholder yang dilakukan PT SOG Indonesia yaitu 1) Pengelolaan Stakeholder (Employee); 2) Recruitment staff; 3) Service Excellent; 4) consumer proximity; 5) social media management; 6) optimizing electronic services.